Overcoming Barriers: Describing Cattle Producers’ Motivations & Perceived Barriers Toward Adopting Sustainable Practices to Inform Communication Strategy - Kindle G. Catching; Ginger Orton; Laura Morgan Fischer (Journal of Applied Communications, 2024)
Sustainability has continued to be a focal point of the cattle industry, as both on-farm and public pressures demand increased attention to the three pillars of sustainability: social, environmental, and economic. The adoption of sustainable practices relies on producers’ acceptance and increased integration on their operations. In this study, we applied the Theory of Diffusion of Innovations and social marketing framework to assess cattle producers’ outcome perceptions, adoption status, and perceived benefits and barriers toward adopting sustainable practices to inform communication campaigns promoting holistic sustainability. An intercept survey was distributed to producers attending a national cattle convention to gain quantitative data. Results indicated producers have the highest intent to adopt practices focused on supporting the local economy, maintaining the overall welfare of cattle, and preserving ranching culture. Additionally, producers viewed protecting water quality, protecting the welfare of cattle, and maintaining healthy ecosystems as the top benefits to adopting sustainable practices on their operation; whereas, financial concerns and risks, changes to equipment and technology, and perceptions of inefficacy were viewed as barriers toward implementation. Communication to cattle producers should focus on how adoption can elevate their perceived benefits and minimize reported barriers. Additional research should focus on continued approaches to understand the types of information cattle producers need to further explain communication strategy in this area by qualitative approaches and message testing. Furthermore, implementing social marketing in the classroom is recommended to equip students with techniques that identify a target audience’s barriers and benefits to inform effective communication campaigns that promote long-lasting behavior change.
Keywords: Diffusion of Innovations; Social Marketing; Benefits; Barriers; Sustainability; Behavior Change